The Influence of Mental Accounting and Fintech on the Savings Behavior of Female Students at Al-Amien in Strengthening Digital Islamic Finance - Imam Buchari; Nina Kurniawati (al-Afkar, Journal For Islamic Studies, 2026)
The growth of fintech has driven the expansion of digital Islamic finance at TMI Al-Amien Prenduan through a fingerprint system and digital savings features. This system supports cashless transactions, effective financial management, and the development of savings habits in accordance with Sharia principles. In this context, mental accounting influences how female students manage and allocate their money, while fintech simplifies the digital savings process. Both play a crucial role in shaping the female students’ savings behavior to be more planned and disciplined. This study aims to analyze: (1) the influence of mental accounting on the saving behavior of Al-Amien female students, (2) the influence of fintech usage on the saving behavior of Al-Amien female students, and (3) the combined influence of mental accounting and fintech usage on the saving behavior of Al-Amien female students. This study employs a quantitative approach with an associative research design. The population of this study consists of all female students at TMI Al-Amien Prenduan, with a sample size of 90 respondents selected using a specific sampling technique. Data collection was conducted via a questionnaire based on indicators of mental accounting, fintech usage, and saving behavior. The data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests. The results of the study indicate that mental accounting has a positive and significant effect on the female students’ saving behavior. The use of fintech also has a positive and significant effect on saving behavior. Simultaneously, both variables were found to have a significant effect on female boarding school students’ saving behavior in supporting the strengthening of a digital-based Islamic financial system. These findings indicate that the ability to manage finances through mental accounting and the utilization of fingerprint-based fintech play a crucial role in fostering more structured, disciplined saving habits that align with Islamic financial principles.